LightRing: Always-Available 2D Input on Any Surface - Kienzle, Wolf; Hinckley, Ken (UIST '14 Proceedings of the 27th annual ACM symposium on User interface software and technology, 2014)
We present LightRing, a wearable sensor in a ring form factor that senses the 2d location of a fingertip on any surface, independent of orientation or material. The device consists of an infrared proximity sensor for measuring finger flexion and a 1-axis gyroscope for measuring finger rotation. Notably, LightRing tracks subtle fingertip movements from the finger base without requiring instrumentation of other body parts or the environment. This keeps the normal hand function intact and allows for a socially acceptable appearance. We evaluate LightRing in a 2d pointing experiment in two scenarios: on a desk while sitting down, and on the leg while standing. Our results indicate that the device has potential to enable a variety of rich mobile input scenarios.